Curso Arumã e formação de professores na Amazônia: contributos para a educação especial - Braga, Waldeilson Martins (2024)
One of the most fundamental questions when we deal with special education, conceiveing it as a way to fight against the exclusion process that has marked the entire history of people with disabilities, in a school context, concerns the role of teacher formation. Whether in the formation of graduate students or in the training of teachers in the field of action, this training, in addition to mastering techniques, didactics and pedagogical resources, must seek, mainly, a change of mentality in relation to disability, which, in turn, implies the deconstruction of concepts, visions, and school cultural practices that limit inclusive action. So, actions that have the emphsis in the teachers formation from the perspective os special education in an inclusive vision assume a responsability in this scenario, once offering a course of this nature is expected to enable those who mainly do so to rethink themselves as teachers, reflecting this reflexive action in pedagogical and school practices from then on in favor of social inclusion. In this way when we are treating with the formation of teachers in the perspective of inclusive education, we took the course called ARUMÃ/IFAM on the Manaus-Center campus, Instituto Federal do Amazonas, in an improvement format, that promoted in its editions, the direct formation of teachers and others education professionals as well as in capital and the countryside of the Amazonas state and Pará, reaching municipalities such as Iranduba, Presidente Figueiredo and Oriximiná. This work focused on offering the Arumã course in the period between 2010 and 2015, trying to answer the central question: What perspectives on special education were worked on with teachers who experienced a formation process offered by the Arumã/IFAM course? By the exposed, this research , a study case, in a qualitative approach, intended to investigate the scope of this formation, presenting an overview of the training offered by the Arumã course to teachers of basic education in special education, considering its formative proposal, in the documents referring to the editions of the course in the period in question. As a result, we may affirm that the actions of the Arumã helped to fill the gap in the inclusive process, that is, the formation of professionals for pedagogical work with special education stakeholders, so this research brings as a proposal for an educational product a curricular component to be included in teacher formation, entitled “Topics of Inclusive Literature and Deaf Literature”.